The Changing Conceptual Framework of the Urban Landscape: Reflections on Ankara - Funda BAŞ BÜTÜNER; Selin ÇAVDAR SERT (Ankara Araştırmaları Dergisi, 2021)
The integrated designed landscape of Ankara’s Republican period has now been replaced by fragmented and repetitive landscapes. This change has introduced a destructive process that has significantly damaged the fabric of the city’s characteristic landscapes, and has obscured their existing value. This article considers two linear landscapes that present different scales, contexts, and spatial types of Ankara’s abraded and lost landscapes: Atatürk Boulevard and Hatip Creek valley. Examination of these two landscapes, which differ in their morphological structures and forms, enables a reconsideration, through an integrated lens, of the characteristic spaces and lost diversity of Ankara’s landscapes. Such a reading also raises awareness of the potential of currently existing areas for landscape production. It is suggested that the landscape-based urbanism that has been considered by many world cities during the last 20-30 years to cope with climate change and preserve the cities should also be applied to Ankara.